Olivia Bloechl, Melanie Lowe and Jeffrey Kallberg (eds), Rethinking Difference in Music Scholarship (2015) - Haworth, Catherine (Journal of the Society for Musicology in Ireland, 2017)
A review of Olivia Bloechl, Melanie Lowe and Jeffrey Kallberg (eds), Rethinking Difference in Music Scholarship (Cambridge: Cambridge University Press, 2015), ISBN 978-1-107-02667-4.